Metachronous anal metastasis from rectal cancer - TERASAWA, Muga; KUBO, Kouichirou; HASEGAWA, Kei; SAITOU, Takaaki; FUJIKAWA, Koichi; WATANABE, Hidejirou (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2012)
A 67-year-old man underwent low anterior resection for rectal cancer in August 2009. Fifteen months after his initial surgery, he complained of anal bleeding. Colonoscopic findings showed that two tumors were located on the anus. We suspected the tumors were metastasis from the rectal cancer, and performed local resection. Histopathological examination revealed the tumors were well differentiated adenocarcinoma and similar to that of the previous rectal cancer. Furthermore, the edge of the tumors were covered with squamous cells, so we diagnosed the tumors as metastasis from the primary rectal cancer.